2018
DOI: 10.1016/j.ecoenv.2018.09.110
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, pollution, bioaccumulation, and ecological risks of trace elements in soils of the northeastern Qinghai-Tibet Plateau

Abstract: Environmental quality of the northeastern Qinghai-Tibet Plateau has attracted more attention due to increasing anthropogenic disturbance. Therefore, this study investigated the distribution, pollution, ecological risks, and bioaccumulation of 12 target heavy metals and 16 rare earth elements (REEs) in soils of this area. The average concentrations of target trace elements in soils ranged from 0.16 (Hg) to 500.46 (Cr) mg/kg. Pb caused more serious pollution than the other elements based on geo-accumulation inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 54 publications
8
47
1
1
Order By: Relevance
“…The average environmentally available REE contents of the investigated soils ranged from 85 to 191 mg kg −1 ( Table 1). These values were similar to those reported for an area in China (average of 179 mg kg −1 ) that is far from large populations, urbanization, and industrialization [27]. In the five studied soil samples, we only observed LREE enrichment in A1 (tonalite bedrock), A2 (pyroxenite bedrock), and B1 (ferrocarbonatite bedrock).…”
Section: Unitssupporting
confidence: 89%
See 1 more Smart Citation
“…The average environmentally available REE contents of the investigated soils ranged from 85 to 191 mg kg −1 ( Table 1). These values were similar to those reported for an area in China (average of 179 mg kg −1 ) that is far from large populations, urbanization, and industrialization [27]. In the five studied soil samples, we only observed LREE enrichment in A1 (tonalite bedrock), A2 (pyroxenite bedrock), and B1 (ferrocarbonatite bedrock).…”
Section: Unitssupporting
confidence: 89%
“…In addition, elements can display different biogeochemical behaviors in natural weathering environments, and therefore differences in individual REE distributions are common [28]. Cerium was the most concentrated REE in the investigated soils, which is consistent with its natural predominance in the environment [27,29]. Even though the REE contents of the plant tissues presented in this study exceeded the limit of detection (Table S1), they were rather low and should therefore be interpreted carefully.…”
Section: Unitssupporting
confidence: 73%
“…Based on a RI ranking criterion [17], thus far all the samples exhibited low ecological risk. Because of river transport and sedimentation, the elemental concentration in the sediments was diluted compared to that in soils as reported by Wu et al [26] and Li et al [37], whose results showed high potential and considerable ecological and health risks near our research area. Moreover, Wang [68] also found low ecological risk and increasing trend of RI in the Lake Qinghai, which is in the northeastern Qinghai-Tibet Plateau, as well as having more anthropogenic disturbances because of tourism.…”
Section: Pollution and Ecological Assessmentsupporting
confidence: 56%
“…For example, Wu et al [26] concluded that there was serious pollution in soils from the northeastern Qinghai-Tibet Plateau which exerted high potential ecological and health risks. Li et al [37] found that the soils in the salt-lake area presented considerable ecological risks in the northeastern Qinghai-Tibet Plateau. The environmental changes due to industrial mining activities of the salt lake and urbanization of the Golmud are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal contamination of soils coming from industry or agriculture, such as smelting industries, residues from nonferrous metal mining, pesticides, fertilizers, municipal composts, are among the major environmental challenges in the world [1][2][3][4][5][6]. Excessive metal concentrations in the contaminated soils can result in soil quality degradation, crop yield reduction, and poor quality of agriculture products [7].…”
Section: Introductionmentioning
confidence: 99%